(untitled) (Journal of Guidance and Counselling Studies, 2025)
The study investigated the influence of psychologically informed motivational strategies on teacher commitment in public secondary schools in Awka North Local Government Area (LGA) of Anambra State. Specifically, the study examined the influence of financial incentives, recognition of teachers’ achievements, and supportive working environment on teacher commitment. The study was guided by four research questions and four null hypotheses tested at 0.05 level of significance. A correlational survey research design was adopted for the study. A total 486 participants were drawn for the study using census sampling of the whole population of teacher and principals in the study area. Data were collected using a structured questionnaire titled “Psychologically Informed Motivational Strategies (PIMS) and Teacher Commitment Questionnaire (TCQ)”, which was developed by the researcher. The instrument was subjected to face validation by three experts in Department of Educational Foundations. The reliability of the instruments was determined using Cronbach’s Alpha method, and a reliability coefficient of 0.78 for PIMS and 0.87 for TCQ) was obtained, indicating high internal consistency. The data were collected through direct administration of the questionnaire and analyzed using the Statistical Package for Social Sciences (SPSS) version 23. Pearson Product Moment Correlation Coefficient was used to answer the research questions and test the null hypotheses. Findings revealed that financial incentives, recognition of achievements, and a supportive working environment each had a significant moderate positive influence on teacher commitment. The study also found a significant joint influence of these motivational strategies on teacher commitment. It was concluded that the implementation of psychologically informed motivational strategies plays a critical role in enhancing teacher commitment in secondary schools. Based on the findings, the study recommended that government and school administrators should ensure timely provision of adequate financial incentives, establish structured teacher recognition programs, and foster supportive working environments. The study further recommended capacity-building programs for school leaders and the institutionalization of motivational strategies through education policy for sustainable teacher commitment and improved school performance.